Reading the present in the Qumran library: the perception of the contemporary by means of scriptural interpretations - De Troyer, Kristin; Lange, Armin (Society of biblical literature symposium series, 2005)
How did ancient scribes interpret their own reality by means of scriptural exegesis? The essays in this volume explore this question from various perspectives by examining the earliest known exegetical texts of Jewish origin, namely, the exegetical texts from the Qumran library. Scholars have debated the precise nature of the exegetical techniques used in the Qumran texts. To bring clarity to the discussion, this book analyzes the phenomenon of reading the present in the Qumran library and asks how far comparable phenomena can be observed in authoritative literature in ancient Israel and Judah, in the textual tradition of the Hebrew and Greek Bible, in ancient Judaism, and in early Christian literature. --From publisher's description